A populist turn? - Ekman Mattias; Krzyżanowski Michał (Nordicom Review)
This article undertakes a critical discourse analysis of Swedish quality newspaper editorials and their evolving framing of immigration since the 2015 peak of the recent European “refugee crisis”. Positioned within the ongoing discursive shifts in the Swedish public sphere and the growth of discursive uncivility in its mainstream areas, the analysis highlights how xenophobic and racist discourses once propagated by the far and radical right gradually penetrate into the studied broadsheet newspapers. We argue that the examined editorials carry the tendency to normalise once radical perceptions of immigration. This takes place by incorporating various discursive strategies embedded in wider argumentative frames – or topoi – of demographic consequences, Islam and Islamisation, threat, and integration. All of these enable constructing claims against immigration now apparently prevalent in the examined strands of the Swedish “quality” press.